Regulatory Property: The New IP - Feldman, Robin (The Columbia Journal of Law & the Arts, 2016)
For almost thirty years, a new form of intellectual property has grown up quietly beneath the surface of societal observation. It is a set of government-granted rights that have the quintessential characteristic of intellectual property and other forms of property—that is, the right to exclude others from the territory. Beginning with a small piece of legislation in the early 1980s, the system now has tentacles stretching out in many directions. It spans more than half a dozen smaller arrangements—established through individual pieces of congressional legislation or regulatory action—and confers hundreds of billions of dollars on those who can fold themselves within its various definitions. Its impact on the United States health care system, in particular, is enormous. In 2015 alone, more than 40 percent of all new drugs approved by the Federal Drug Administration (the “FDA”) came through just one of these portals, with the companies collecting regulatory property rights along the way.